Precedent predictions and present practice - Elnerine Greef (Communicare)
The economic reality of South Africa is that the industries responsible for the greatest contribution to the country’s Gross Domestic Product are also those responsible for the greatest loss of life among their employee population. The South African mining and construction industries are notoriously dangerous and were responsible for the loss of more than 200 employees’ lives in 2011 – an improvement over previous years. This notwithstanding, many organisations still think that occupational safety is an ethical consideration that either impedes or hampers business outputs. This notion is one that stakeholder theory regards to be a fallacy, specifically the separation fallacy, one that is in need of rejection and replacement by the integrated thesis, which proposes that the term business ethics no longer be seen as an oxymoron but rather as tautology. In this article, the significance of this proposition will be outlined, as empirically tested within the mining and construction industries of South Africa at two organisations – the Gautrain Project (predominantly located within the construction industry) and Diesel Power Opencast Mining (predominantly located within the mining industry